2011
DOI: 10.1096/fj.10-179895
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone drives fetal cardiomyocyte maturation

Abstract: Tri-iodo-l-thyronine (T(3)) suppresses the proliferation of near-term serum-stimulated fetal ovine cardiomyocytes in vitro. Thus, we hypothesized that T(3) is a major stimulant of cardiomyocyte maturation in vivo. We studied 3 groups of sheep fetuses on gestational days 125-130 (term ∼145 d): a T(3)-infusion group, to mimic fetal term levels (plasma T(3) levels increased from ∼0.1 to ∼1.0 ng/ml; t(1/2)∼24 h); a thyroidectomized group, to produce low thyroid hormone levels; and a vehicle-infusion group, to serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 91 publications
(114 reference statements)
5
145
0
1
Order By: Relevance
“…Because PPARA/PPARGC1A is known to be regulated by or interact with the thyroid hormone pathway, [32][33][34][35] which promotes the maturation of fetal VCMs and ESC-CMs, 36,37 we then examined the functional consequences of T3 treatment on contractile forces. Although shortening of single hESCCMs or their clusters has been measured as an surrogate index for contractile forces, 38,39 a multicellular 3D hvCMT system has been developed, where true dynamic tension developed by the tissue in real time can be measured.…”
Section: T3 Treatment Increases the Contractile Forces Of Engineered mentioning
confidence: 99%
“…Because PPARA/PPARGC1A is known to be regulated by or interact with the thyroid hormone pathway, [32][33][34][35] which promotes the maturation of fetal VCMs and ESC-CMs, 36,37 we then examined the functional consequences of T3 treatment on contractile forces. Although shortening of single hESCCMs or their clusters has been measured as an surrogate index for contractile forces, 38,39 a multicellular 3D hvCMT system has been developed, where true dynamic tension developed by the tissue in real time can be measured.…”
Section: T3 Treatment Increases the Contractile Forces Of Engineered mentioning
confidence: 99%
“…Our contention that T3 triggers the postnatal CM hyperplastic response during maturational heart growth is not always, at first glance, consistent with earlier reports. For example, Chattergoon et al (2012) evaluated the effects on fetal CM maturation of T3 given to sheep by infusion on gestational days 125-130 (term~145 days). These studies suggested that T3 augments CM maturation, as evidenced by increases in cell width, binucleation and expression of the cell cycle inhibitor, p21, as well as by reductions in cyclin D1 and in cell proliferation.…”
Section: Cardiac Morphologymentioning
confidence: 99%
“…On the other side, regulators of the cell cycle were altered in chicken embryos following highglucose treatment, while resveratrol reversed the alteration. When chicken embryos were exposed to high-glucose environment, embryonic cells may have been arrested in the G1 phase because of the suppression of cyclin D1 and the upregulation of p21 [17], which would lead to a reduction of embryonic cell proliferation. We can suspect that the effect of resveratrol may also be related to its activity on these regulators.…”
Section: Discussionmentioning
confidence: 99%